Optical laminate body and image display device
Patent Information
- Application Number
- JP2023128065
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-17
AI Technical Summary
【0006】 本発明の実施形態によれば、画像表示装置に適用した場合、高温環境下における表示ムラを抑制し得る光学積層体を実現することができる。
Smart Images

Figure 2025023700000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical laminate and an image display device. [Background technology]
[0002] In recent years, image display devices such as liquid crystal display devices and electroluminescence (EL) display devices (for example, organic EL display devices and inorganic EL display devices) have rapidly become widespread. In many image display devices, an optical laminate including a retardation film (for example, an anti-reflection film in which a polarizing plate and a retardation film are integrated) is used. In recent years, as the demand for thinner image display devices has increased, the demand for thinner optical laminates has also increased. In order to reduce the thickness of optical laminates, the retardation layer (retardation film), which contributes greatly to the thickness, has been made thinner. A representative example of a thin retardation film is a film in which a liquid crystal compound is oriented and the oriented state is fixed (hereinafter referred to as a liquid crystal film). Since the birefringence (Δn) of a liquid crystal compound is significantly larger than that of a resin, the thickness of the liquid crystal film to obtain a desired in-plane retardation can be made significantly smaller than that of a stretched film of a resin film. However, when an optical laminate using a liquid crystal film is applied to an image display device, the display unevenness may become large under a high temperature environment. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-222282 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has been made to solve the above-mentioned problems in the conventional art, and its main object is to provide an optical laminate that can suppress display unevenness in a high-temperature environment when applied to an image display device. [Means for solving the problem]
[0005] [1] An optical laminate according to an embodiment of the present invention has, in this order, a polarizing plate including a polarizer, a first retardation layer, a second retardation layer, and a pressure-sensitive adhesive layer; the first retardation layer and the second retardation layer are each a liquid crystal alignment solidified layer; and a thickness T of the polarizer and a storage modulus E of the pressure-sensitive adhesive layer satisfy the following relationship: T / E≦0.100(μm / kPa). [2] In the above [1], the optical laminate has a sum of a shrinkage percentage in a first direction and a shrinkage percentage in a second direction perpendicular to the first direction of 0.80% or less after heating at 85°C for 240 hours. [3] In the above [1] or [2], the pressure-sensitive adhesive layer has a storage modulus E of 70 kPa or more and / or the polarizer has a thickness T of 8 μm or less. [4] In any of the above [1] to [3], the first retardation layer has Re(550) of 200 nm to 300 nm, and the angle between its slow axis and the absorption axis of the polarizer is 10° to 20°; the second retardation layer has Re(550) of 100 nm to 190 nm, and the angle between its slow axis and the absorption axis of the polarizer is 70° to 80°. [5] In any one of [1] to [4] above, the optical laminate further has a third retardation layer between the polarizing plate and the pressure-sensitive adhesive layer, the refractive index characteristics of which satisfy the relationship nz>nx=ny. [6] According to another aspect of the present invention, there is provided an image display device, the image display device comprising the optical laminate according to any one of [1] to [5] above. Effect of the Invention
[0006] According to the embodiment of the present invention, it is possible to realize an optical laminate that can suppress display unevenness in a high-temperature environment when applied to an image display device. [Brief description of the drawings]
[0007] [Figure 1] 1 is a schematic cross-sectional view of an optical laminate according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Representative embodiments of the present invention will be described below, but the present invention is not limited to these embodiments.
[0009] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation of a film measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation of a film measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re=(nx-ny)×d, where d(nm) is the thickness of the film. (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction of a film measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction of a film measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth=(nx-nz)×d, where d(nm) is the thickness of the film. (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, unless otherwise specified, the angles include angles in both clockwise and counterclockwise directions.
[0010] A. Optical laminate FIG. 1 is a schematic cross-sectional view of an optical laminate according to one embodiment of the present invention. The optical laminate 100 in the illustrated example has a polarizing plate 10, a first retardation layer 21, a second retardation layer 22, and an adhesive layer 30 in this order from the upper side of the drawing. The upper side of the drawing is the viewing side, and the lower side of the drawing is the image display panel side. The adhesive layer 30 enables the optical laminate to be attached to the image display panel. The polarizing plate 10 includes a polarizer 11 and a protective layer 12 disposed on one side of the polarizer 11 (the viewing side in the illustrated example). The polarizing plate in the illustrated example is a so-called single-protection polarizing plate. Depending on the purpose, another protective layer (inner protective layer: not shown) may be disposed on the side opposite to the protective layer 12 of the polarizer 11. That is, the polarizing plate may be a double-protection polarizing plate. From the viewpoint of thinning the optical laminate, the inner protective layer can be omitted.
[0011] The first retardation layer 21 and the second retardation layer 22 are each a liquid crystal alignment cured layer. By using the liquid crystal alignment cured layer as the retardation layer, a desired in-plane retardation can be realized with a thickness significantly thinner than that of a stretched film of a resin film. As a result, significant thinning of the optical laminate can be achieved. Typically, the first retardation layer 21 and the second retardation layer 22, as a laminate thereof, have a circular polarization function or an elliptical polarization function, and have a relationship of Re(450) < Re(550) < Re(650). That is, the retardation layer 21 and the second retardation layer 22, as a laminate thereof, typically exhibit an inverse-dispersion wavelength dependence in which the retardation value increases with the wavelength of the measurement light. With such a configuration, a good antireflection function can be realized in a very wide wavelength band. In the present specification, the "liquid crystal alignment cured layer" refers to a layer in which a liquid crystal compound is aligned in a predetermined direction within the layer and the alignment state is fixed. The "liquid crystal alignment cured layer" is a concept that includes an alignment cured layer obtained by curing a liquid crystal monomer.
[0012] In the embodiment of the present invention, the thickness T of the polarizer 11 and the storage elastic modulus E of the adhesive layer 30 satisfy the following relationship. T / E ≦ 0.100 (μm / kPa) With such a configuration, when the optical laminate is applied to an image display device, display unevenness in a high-temperature environment can be suppressed. T / E is preferably 0.090 (μm / kPa) or less, more preferably 0.080 (μm / kPa) or less, even more preferably 0.070 (μm / kPa) or less, and particularly preferably 0.065 (μm / kPa) or less. Meanwhile, T / E is preferably 0.015 (μm / kPa) or more, more preferably 0.020 (μm / kPa) or more, and even more preferably 0.025 (μm / kPa) or more. The present inventors have intensively studied the relationship between the optical laminate including the liquid crystal alignment solidified layer and the display unevenness in a high-temperature environment of an image display device to which the optical laminate is applied, and have found that one of the factors is the shift of the slow axis of the liquid crystal alignment solidified layer caused by the thermal shrinkage of the polarizing plate. Furthermore, after repeated trial and error to find a solution to such problems, it was found that by optimizing the combination of the thickness of the polarizer and the storage modulus of the adhesive layer (or the adhesive constituting the adhesive), it is possible to suppress the shift of the slow axis of the liquid crystal alignment solidified layer, and as a result, it is possible to suppress display unevenness in a high temperature environment of an image display device. Furthermore, it was found that the desired results cannot be obtained by adjusting the thickness of the polarizer or the storage modulus of the adhesive layer alone. Therefore, the effects of the embodiments of the present invention are unexpectedly excellent effects.
[0013] In one embodiment, the sum of the shrinkage rate in the first direction and the shrinkage rate in the second direction perpendicular to the first direction of the optical laminate after heating at 85°C for 240 hours is preferably 0.80% or less, more preferably 0.75% or less, even more preferably 0.70% or less, and particularly preferably 0.65% or less. On the other hand, the sum is preferably 0.30% or more, more preferably 0.35% or more, and even more preferably 0.40% or more. With such a configuration, it is easy to achieve the desired T / E. The smaller the difference (absolute value) between the shrinkage rate in the first direction and the shrinkage rate in the second direction of the optical laminate after heating at 85°C for 240 hours, the more preferable it is. The difference (absolute value) may be, for example, 0.08% or less, or, for example, 0.07% or less, or, for example, zero. With such a configuration, the effect of the embodiment of the present invention may be remarkable. The first direction may be the absorption axis direction of the polarizer, the transmission axis direction of the polarizer, or a direction having a predetermined angle (e.g., 45°, 135°) with respect to the absorption axis of the polarizer.
[0014] In one embodiment, the optical laminate may further include a third retardation layer (not shown) between the polarizing plate 10 and the adhesive layer 30. The third retardation layer typically exhibits a refractive index characteristic of nz>nx=ny. By providing such a third retardation layer, it is possible to effectively prevent reflection in an oblique direction, and to achieve a wide viewing angle of the anti-reflection function. The third retardation layer may typically be provided between the second retardation layer 22 and the adhesive layer 30.
[0015] For practical purposes, it is preferable that a release liner is temporarily attached to the surface of the pressure-sensitive adhesive layer 30 until the optical laminate is used. By temporarily attaching the release liner, the pressure-sensitive adhesive layer is protected and the optical laminate can be formed into a roll.
[0016] The components of the optical laminate will be specifically described below.
[0017] B. Polarizing plate B-1.Polarizer The polarizer 11 is typically made of a polyvinyl alcohol (PVA) resin film containing a dichroic material (e.g., iodine). Examples of PVA resins include polyvinyl alcohol, partially formalized polyvinyl alcohol, ethylene-vinyl alcohol copolymer, and partially saponified ethylene-vinyl acetate copolymer.
[0018] The PVA-based resin preferably contains an acetoacetyl-modified PVA-based resin. With this configuration, a polarizer having desired mechanical strength can be obtained. The amount of the acetoacetyl-modified PVA-based resin is preferably 5% by weight to 20% by weight, and more preferably 8% by weight to 12% by weight, based on 100% by weight of the entire PVA-based resin. If the amount is within this range, a polarizer having better mechanical strength can be obtained.
[0019] The polarizer preferably contains iodide or sodium chloride (sometimes collectively referred to as halide). Examples of iodide include potassium iodide, sodium iodide, and lithium iodide. The content of the halide in the polarizer is preferably 5 to 20 parts by weight, more preferably 10 to 15 parts by weight, based on 100 parts by weight of the PVA-based resin. In the manufacturing method described below, the halide can be blended in a coating liquid that forms a PVA-based resin layer, which is a precursor of the polarizer, and finally introduced into the polarizer. By introducing a halide into the polarizer, the orientation of the PVA molecules in the polarizer can be increased, and therefore a polarizer having excellent optical properties (typically, both a high polarization degree and a high single transmittance) can be realized.
[0020] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is preferably 41.0% to 46.0%, and more preferably 42.0% to 45.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more. According to the embodiment of the present invention, even if the single transmittance is in the above range, the degree of polarization can be maintained in such a range.
[0021] The thickness of the polarizer is, for example, 12 μm or less, preferably 10 μm or less, more preferably 1 μm to 8 μm, and further preferably 3 μm to 7 μm. By combining such a thin polarizer with a liquid crystal alignment solidified layer, it is possible to significantly reduce the thickness of the optical laminate. Furthermore, if the thickness of the polarizer is within the above range, curling during heating can be well suppressed, and good appearance durability during heating can be obtained.
[0022] The polarizer can be produced by any appropriate method. For example, the resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.
[0023] Specific examples of polarizers made of a single-layer resin film include hydrophilic polymer films such as PVA films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films that have been dyed with iodine or a dichroic substance such as a dichroic dye and stretched, and polyene-based oriented films such as dehydrated PVA films and dehydrochlorinated polyvinyl chloride films. A polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching it is preferably used because of its excellent optical properties.
[0024] The dyeing with iodine is carried out, for example, by immersing the PVA-based film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment, or may be carried out while dyeing. Alternatively, the film may be stretched and then dyed. If necessary, the PVA-based film may be subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like. For example, by immersing the PVA-based film in water and washing it with water before dyeing, it is possible to wash off dirt and antiblocking agents on the surface of the PVA-based film, and also to swell the PVA-based film and prevent uneven dyeing.
[0025] Specific examples of polarizers obtained using a laminate include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, the laminate is preferably subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. Typically, the manufacturing method of this embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of the PVA, and to achieve high optical properties. In addition, by simultaneously increasing the orientation of the PVA in advance, problems such as a decrease in the orientation of the PVA or dissolution when immersed in water in the subsequent dyeing and stretching steps can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation of the polyvinyl alcohol molecules can be disturbed and the orientation can be reduced, compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of a polarizer obtained by immersing the laminate in a liquid through a treatment process such as a dyeing treatment and an underwater stretching treatment. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction through a drying shrinkage treatment.The obtained resin substrate / polarizer laminate may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or any suitable protective layer may be laminated on the peeled surface of the resin substrate / polarizer laminate after peeling the resin substrate from the resin substrate / polarizer laminate, or on the surface opposite to the peeled surface, depending on the purpose. Details of the method for producing such a polarizer are described in, for example, JP2012-73580A and JP6470455A. The entire disclosures of these publications are incorporated herein by reference.
[0026] B-2.Protective layer The protective layer 12 and the inner protective layer (if present) are composed of any suitable resin film. Representative materials for the resin film include cellulose-based resins such as triacetyl cellulose (TAC), cycloolefin-based resins such as polynorbornene, (meth)acrylic resins, polyester-based resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polyolefin-based resins such as polyethylene, and polycarbonate-based resins. Representative examples of (meth)acrylic resins include (meth)acrylic resins having a lactone ring structure. (Meth)acrylic resins having a lactone ring structure are described in, for example, JP-A-2000-230016, JP-A-2001-151814, JP-A-2002-120326, JP-A-2002-254544, and JP-A-2005-146084. These publications are incorporated herein by reference. From the viewpoint of ease of processing into irregular shapes, etc., cellulose-based resins are preferred, and TAC is more preferred. From the viewpoint of obtaining a polarizing plate having low moisture permeability and excellent durability, cycloolefin-based resins and (meth)acrylic resins are preferred.
[0027] The optical laminate is typically placed on the viewing side of an image display device, and the protective layer 12 is typically placed on the viewing side. Therefore, the protective layer 12 may be subjected to a surface treatment as necessary. Examples of the surface treatment include hard coat treatment, anti-reflection treatment, anti-sticking treatment, and anti-glare treatment. Furthermore, the protective layer 12 may be subjected to a treatment for improving visibility when viewed through polarized sunglasses (typically, imparting an (elliptical) polarizing function or imparting an ultra-high phase difference) as necessary. By performing such treatment, excellent visibility can be achieved even when the display screen is viewed through polarized lenses such as polarized sunglasses. Therefore, the optical laminate can be suitably applied to image display devices that can be used outdoors.
[0028] In one embodiment, the inner protective layer (if present) is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm, and the retardation in the thickness direction Rth(550) is -10 nm to +10 nm.
[0029] The thickness of the protective layer 12 and the inner protective layer (if present) is preferably 10 μm to 80 μm, more preferably 12 μm to 40 μm, and further preferably 15 μm to 35 μm. When the protective layer 12 is surface-treated, the thickness of the protective layer 12 includes the thickness of the surface treatment layer.
[0030] C. First retardation layer and second retardation layer As described above, the first retardation layer 21 and the second retardation layer 22 are each a liquid crystal alignment solidified layer. In this section, when the first retardation layer 21 and the second retardation layer 22 are collectively described, they are simply described as a "retardation layer" or a "liquid crystal alignment solidified layer".
[0031] Examples of the liquid crystal compound used in the liquid crystal alignment solidified layer include liquid crystal polymers and liquid crystal monomers. The liquid crystal compound is preferably polymerizable (i.e., liquid crystal monomer). If the liquid crystal compound is polymerizable, the alignment state of the liquid crystal compound can be fixed by aligning the liquid crystal compound and then polymerizing it. Here, the polymer formed by polymerization is non-liquid crystal. Therefore, the formed liquid crystal alignment solidified layer does not undergo transition to a liquid crystal phase, a glass phase, or a crystalline phase due to temperature changes that are specific to liquid crystal compounds. As a result, the liquid crystal alignment solidified layer becomes a retardation layer that is not affected by temperature changes and has extremely excellent stability.
[0032] In one embodiment, the liquid crystal alignment solidified layer may be formed using a composition containing a polymerizable liquid crystal compound (polymerizable liquid crystal compound, i.e., liquid crystal monomer). In this specification, the polymerizable liquid crystal compound contained in the composition refers to a compound having a polymerizable group and liquid crystal properties. The polymerizable group means a group involved in a polymerization reaction, and is preferably a photopolymerizable group. Here, the photopolymerizable group refers to a group that can be involved in a polymerization reaction by an active radical or acid generated from a photopolymerization initiator. As the liquid crystal monomer, for example, polymerizable mesogen compounds described in JP-A-2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445, etc., can be used. Specific examples of such polymerizable mesogenic compounds include LC242 (trade name) from BASF, E7 (trade name) from Merck, and LC-Sillicon-CC3767 (trade name) from Wacker-Chem.
[0033] The mechanism by which the liquid crystal compound exhibits liquid crystallinity may be thermotropic or lyotropic. The liquid crystal phase may be nematic or smectic. From the viewpoint of ease of production, the liquid crystallinity is preferably thermotropic nematic liquid crystal.
[0034] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on its type. Specifically, the temperature range is preferably from 40°C to 120°C, more preferably from 50°C to 100°C, and most preferably from 60°C to 90°C.
[0035] The birefringence Δn of the liquid crystal alignment curing layer is preferably 0.06 or more, more preferably 0.08 or more, still more preferably 0.09 or more, and particularly preferably 0.10 or more. The upper limit of Δn can be, for example, 0.13 or can be, for example, 0.12. If Δn is within such a range, a desired in-plane retardation can be achieved with a very thin thickness. As a result, the liquid crystal alignment curing layer and the optical laminate can be made thinner, and ultimately, it can contribute to a significant thinning of the image display device.
[0036] The liquid crystal alignment curing layer may exhibit an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light, may exhibit a positive wavelength dispersion characteristic in which the retardation value decreases according to the wavelength of the measurement light, or may exhibit a flat wavelength dispersion characteristic in which the retardation value hardly changes depending on the wavelength of the measurement light.
[0037] Typically, the liquid crystal alignment curing layer shows a refractive index characteristic of nx > ny = nz. Therefore, the liquid crystal alignment curing layer has a slow axis. Note that "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny > nz or ny < nz may occur.
[0038] The first retardation layer 21 can typically function as a λ / 2 plate, and the second retardation layer 22 can typically function as a λ / 4 plate. Specifically, Re(550) of the first retardation layer is preferably 200 nm to 300 nm, more preferably 230 nm to 290 nm, still more preferably 250 nm to 280 nm; Re(550) of the second retardation layer is preferably 100 nm to 190 nm, more preferably 120 nm to 170 nm, still more preferably 130 nm to 150 nm. The thickness of the first retardation layer can be adjusted so as to obtain a desired in-plane retardation of the λ / 2 plate. Specifically, the thickness can be, for example, 2.0 μm to 4.0 μm. The thickness of the second retardation layer can be adjusted so as to obtain a desired in-plane retardation of the λ / 4 plate. Specifically, the thickness can be, for example, 1.0 μm to 2.5 μm. The angle formed between the slow axis of the first retardation layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, still more preferably 14° to 16°; the angle formed between the slow axis of the second retardation layer and the absorption axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, still more preferably 74° to 76°. Note that the arrangement order of the first retardation layer and the second retardation layer may be reversed, and the angle formed between the slow axis of the first retardation layer and the absorption axis of the polarizer and the angle formed between the slow axis of the second retardation layer and the absorption axis of the polarizer may be reversed.
[0039] As described above, the first retardation layer 21 and the second retardation layer 22, as a laminate thereof, have a circular polarization function or an elliptical polarization function and have a relationship of Re(450) < Re(550) < Re(650). That is, the laminate of the first retardation layer 21 and the second retardation layer 22 can function as a λ / 4 plate exhibiting an inverse-dispersion wavelength dependence. Therefore, in one embodiment, the laminate of the first retardation layer 21 and the second retardation layer 22 may be replaced with a single retardation layer (liquid crystal alignment solidified layer) that can function as a λ / 4 plate exhibiting an inverse-dispersion wavelength dependence.
[0040] The single retardation layer (liquid crystal alignment solidified layer) is formed, for example, using a composition containing a liquid crystal compound represented by the following formula (I). L1 -SP 1 -A 1 -D 3 -G 1 -D 1 -Ar-D 2 -G 2 -D 4 -A 2 -SP 2 -L 2 (I)
[0041] L 1 and L 2 each independently represents a monovalent organic group; L 1 and L 2 At least one of L represents a polymerizable group. The monovalent organic group may include any suitable group. 1 and L 2 The polymerizable group represented by at least one of the above may be a radically polymerizable group (a group capable of radical polymerization). Any appropriate radically polymerizable group may be used as the radically polymerizable group. An acryloyl group or a methacryloyl group is preferred. The acryloyl group is preferred from the viewpoint of high polymerization speed and productivity improvement. A methacryloyl group may also be used as a polymerizable group for a high birefringence liquid crystal.
[0042] SP 1 and S.P. 2 each independently represents a single bond, a linear or branched alkylene group, or a divalent linking group in which one or more -CH2- constituting a linear or branched alkylene group having 1 to 14 carbon atoms are substituted with -O-. Preferred examples of the linear or branched alkylene group having 1 to 14 carbon atoms include a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group, and a hexylene group.
[0043] A 1 and A 2 Each of A independently represents an alicyclic hydrocarbon group or an aromatic ring substituent. 1 and A 2 is preferably an aromatic ring substituent having 6 or more carbon atoms or a cycloalkylene ring having 6 or more carbon atoms.
[0044] D 1 , D 2 , D 3 and D. 4 Each independently represents a single bond or a divalent linking group. 1 , D 2 , D 3 and D. 4 is a single bond, -O-CO-, -C(=S)O-, -CR 1 R 2 -, -CR 1 R 2 -CR 3 R 4 -, -O-CR 1 R 2 -, -CR 1 R 2 -O-CR 3 R 4 -,-CO-O-CR 1 R 2 -, -O-CO-CR 1 R 2 -, -CR 1 R 2 -O-CO-CR 3 R 4 -, -CR 1 R 2 -CO-O-CR 3 R 4 -, -NR 1 -CR 2 R 3 -, or -CO-NR 1 -, where D 1 , D 2 , D 3 and D. 4 At least one of the groups represents -O-CO-. 3 is preferably -O-CO-, and D 3 and D. 4 More preferably, is -O-CO-. 1 and D. 2 is preferably a single bond. 1 , R 2 , R 3 and R 4 each independently represents a hydrogen atom, a fluorine atom, or an alkyl group having 1 to 4 carbon atoms.
[0045] G 1 and G 2 Each of G independently represents a single bond or an alicyclic hydrocarbon group. 1 and G 2 may represent an unsubstituted or substituted divalent alicyclic hydrocarbon group having 5 to 8 carbon atoms. In addition, one or more of the -CH2- constituting the alicyclic hydrocarbon group may be substituted with -O-, -S- or -NH-. 1 and G 2 preferably represents a single bond.
[0046] Ar represents an aromatic hydrocarbon ring or an aromatic heterocycle. Ar represents an aromatic ring selected from the group consisting of groups represented by the following formulae (Ar-1) to (Ar-6). In the following formulae (Ar-1) to (Ar-6), *1 represents D 1 *2 indicates the bond position with D 2 represents the bonding position with [ka]
[0047] In formula (Ar-1), Q 1 represents N or CH, and Q 2 is -S-, -O-, or -N(R 5 )-. R 5 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. 1 represents an unsubstituted or substituted aromatic hydrocarbon group having 6 to 12 carbon atoms, or an aromatic heterocyclic group having 3 to 12 carbon atoms.
[0048] In formulas (Ar-1) to (Ar-6), Z 1 , Z 2 and Z 3 each independently represents a hydrogen atom, a monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms, a monovalent alicyclic hydrocarbon group having 3 to 20 carbon atoms, a monovalent aromatic hydrocarbon group having 6 to 20 carbon atoms, a halogen atom, a cyano group, a nitro group, -NR 6 R 7 , or -SR 8Represents R 6 ~R 8 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; Z 1 and Z 2 may be bonded to each other to form a ring. The ring may be any of an alicyclic ring, a heterocyclic ring, and an aromatic ring, and is preferably an aromatic ring. The ring formed may be substituted with a substituent.
[0049] In formulas (Ar-2) and (Ar-3), A 3 and A 4 are each independently -O-, -N(R 9 R represents a group selected from the group consisting of -, -S-, and -CO-; 9 represents a hydrogen atom or a substituent. 9 The substituent represented by the formula (Ar-1) is preferably Y 1 The substituents are the same as those which may be possessed by the group.
[0050] In formula (Ar-2), X represents a hydrogen atom or an unsubstituted or substituted nonmetallic atom of Groups 14 to 16. Examples of the nonmetallic atom of Groups 14 to 16 represented by X include an oxygen atom, a sulfur atom, an unsubstituted or substituted nitrogen atom, and an unsubstituted or substituted carbon atom. Examples of the substituent include Y in formula (Ar-1). 1 The substituents are the same as those which may be possessed by the group.
[0051] In formula (Ar-3), D 5 and D. 6 are each independently a single bond, -O-CO-, -C(=S)O-, or -CR 1 R 2 -, -CR 1 R 2 -CR 3 R 4 -, -O-CR 1 R 2 -, -CR 1 R 2 -O-CR 3 R 4 -,-CO-O-CR 1 R 2-, -O-CO-CR 1 R 2 -, -CR 1 R 2 -O-CO-CR 3 R 4 -, -CR 1 R 2 -CO-O-CR 3 R 4 -, -NR 1 -CR 2 R 3 -, or -CO-NR 1 - stands for R 1 , R 2 , R 3 and R 4 is as stated above.
[0052] In formula (Ar-3), SP 3 and S.P. 4 each independently represents a single bond, a linear or branched alkylene group having 1 to 12 carbon atoms, or a divalent linking group in which one or more -CH2- groups constituting the linear or branched alkylene group having 1 to 12 carbon atoms are substituted with -O-, -S-, -NH-, -N(Q)-, or -CO-, and Q represents a polymerizable group.
[0053] In formula (Ar-3), L 3 and L 4 each independently represents a monovalent organic group; L 3 and L 4 And L in the above formula (1) 1 and L 2 At least one of these represents a polymerizable group.
[0054] In the formulae (Ar-4) to (Ar-6), Ax represents an organic group having 2 to 30 carbon atoms and having at least one aromatic ring selected from the group consisting of aromatic hydrocarbon rings and aromatic heterocycles. In the formulae (Ar-4) to (Ar-6), Ax preferably has an aromatic heterocycle, more preferably has a benzothiazole ring. In the formulae (Ar-4) to (Ar-6), Ay represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms which may be unsubstituted or substituted, or an organic group having 2 to 30 carbon atoms and having at least one aromatic ring selected from the group consisting of aromatic hydrocarbon rings and aromatic heterocycles. In the formulae (Ar-4) to (Ar-6), Ay preferably represents a hydrogen atom.
[0055] In formulas (Ar-4) to (Ar-6), Q 3 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms which may be unsubstituted or substituted. 3 preferably represents a hydrogen atom.
[0056] Of such Ar, preferred are the groups (atomic groups) represented by the above formula (Ar-4) or (Ar-6).
[0057] The liquid crystal compounds may be used alone or in combination. Specific examples of the liquid crystal compounds are described in, for example, JP 2006-163343 A, JP 2006-178389 A, and WO 2018 / 123551 A. The descriptions in these publications are incorporated herein by reference.
[0058] D. Third retardation layer As described above, the third retardation layer has a refractive index characteristic of nz>nx=ny. That is, the third retardation layer is a so-called positive C plate. The thickness direction retardation Rth(550) of the third retardation layer is preferably -50 nm to -300 nm, more preferably -70 nm to -250 nm, further preferably -90 nm to -200 nm, and particularly preferably -100 nm to -180 nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane retardation Re(550) of the third retardation layer can be less than 10 nm.
[0059] The third retardation layer may be formed of any appropriate material. The third retardation layer is preferably made of a film containing a liquid crystal material fixed in homeotropic alignment. The liquid crystal material (liquid crystal compound) that can be homeotropically aligned may be a liquid crystal monomer or a liquid crystal polymer. Specific examples of the liquid crystal compound and the method for forming the retardation layer include the liquid crystal compound and the method for forming the retardation layer described in
[0020] to
[0028] of JP-A-2002-333642. In this case, the thickness of the third retardation layer is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and even more preferably 0.5 μm to 5 μm.
[0060] E. Adhesive layer E-1. Outline of adhesive layer The pressure-sensitive adhesive layer 30 (substantially the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer) preferably has a storage modulus of 70 kPa or more, more preferably 75 kPa to 200 kPa, and even more preferably 80 kPa to 150 kPa at 25° C. If the storage modulus of the pressure-sensitive adhesive layer in a room temperature environment is within this range, the desired T / E can be easily achieved.
[0061] The pressure-sensitive adhesive layer (substantially the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer) preferably has a storage modulus of 40 kPa or more, more preferably 45 kPa to 500 kPa, and even more preferably 50 kPa to 470 kPa at 85° C. If the storage modulus of the pressure-sensitive adhesive layer at high temperatures is within such a range, it is possible to realize an optical laminate that can more effectively suppress display unevenness in a high-temperature environment when applied to an image display device.
[0062] The pressure-sensitive adhesive layer (actually, the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer) preferably has a creep value at 23°C of 200 µm or less, more preferably 5 µm to 150 µm, and even more preferably 10 µm to 100 µm. If the creep value of the pressure-sensitive adhesive layer is within such a range, it may be easy to achieve the desired storage modulus. The creep value can be measured, for example, by the following procedure: A test sample cut out from the pressure-sensitive adhesive sheet is attached to a support plate at a bonding surface of 10 mm x 10 mm. With the support plate to which the test sample is attached being fixed, a load of 500 gf is applied vertically downward. The amount of displacement from the support plate 1 second and 3600 seconds after the load is applied is measured, and Cr1 and Cr 3600 Let Cr1 and Cr 3600 The creep value is determined as ΔCr by the following formula: Note that the creep value in this specification is a value calculated based on a pressure-sensitive adhesive layer thickness of 20 μm. ΔCr=Cr 3600 -Cr1
[0063] The thickness of the pressure-sensitive adhesive layer is preferably 10 μm to 50 μm, more preferably 15 μm to 40 μm. When the thickness of the pressure-sensitive adhesive layer is within such a range, it is possible to realize an optical laminate that can suppress display unevenness in a high-temperature environment when applied to an image display device due to a synergistic effect with the effect of optimizing the T / E.
[0064] The pressure-sensitive adhesive layer may have any suitable structure as long as it can realize the desired T / E. The pressure-sensitive adhesive layer desired in the embodiment of the present invention may be obtained by adjusting the composition of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer (e.g., the type (polarity, Tg, softness) and molecular weight of the base polymer), the crosslinking structure (e.g., the type of crosslinking agent, the distance between crosslinking points (molecular weight between crosslinking points), and the crosslinking density), etc.
[0065] E-2. Adhesive that constitutes the adhesive layer The adhesive constituting the adhesive layer typically contains a base polymer, a crosslinking agent, and, if necessary, a silane coupling agent and / or an additive.
[0066] E-2-1. Base polymer The pressure-sensitive adhesive layer is typically formed from a pressure-sensitive adhesive composition containing a (meth)acrylic polymer, a urethane polymer, a silicone polymer, or a rubber polymer as a base polymer. A preferred base polymer is a (meth)acrylic polymer. The (meth)acrylic polymer contains an alkyl (meth)acrylate as a main monomer component. Here, (meth)acrylic refers to acrylic and / or methacrylic.
[0067] The alkyl (meth)acrylate may be contained in an amount of preferably 50% by weight or more, more preferably 60% by weight or more, even more preferably 70% by weight or more, particularly preferably 80% by weight or more, and especially preferably 90% by weight or more, of all monomer components forming the (meth)acrylic polymer.
[0068] The alkyl (meth)acrylate preferably includes a linear or branched alkyl group having 1 to 18 carbon atoms. The number of carbon atoms in the alkyl group is more preferably 2 to 10, and further preferably 3 to 8. The alkyl (meth)acrylate includes, for example, methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate, cyclohexyl acrylate, 2-ethylhexyl acrylate, and isooctyl acrylate. The alkyl (meth)acrylates can be used alone or in combination.
[0069] The (meth)acrylic polymer may contain a copolymerizable monomer that can be copolymerized with alkyl (meth)acrylate as a monomer component. Examples of the copolymerizable monomer include a carboxyl group-containing monomer and a hydroxyl group-containing monomer. The carboxyl group-containing monomer is a compound that contains a carboxyl group in its structure and a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the carboxyl group-containing monomer include (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Acrylic acid is preferred. The hydroxyl group-containing monomer is a compound that contains a hydroxyl group in its structure and a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of hydroxyl group-containing monomers include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate. 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred. From the viewpoint of adjusting the properties of the adhesive layer, copolymerizable monomers other than those mentioned above may be used. Examples of such copolymerizable monomers include amino group-containing monomers, amide group-containing monomers, polyfunctional monomers, cyclic polymerizable monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, (meth)acrylic acid esters having alicyclic hydrocarbon groups, (meth)acrylic acid esters having aromatic hydrocarbon groups, vinyl esters, aromatic vinyl compounds, olefins, dienes, and vinyl ethers. The copolymerizable monomers can be used alone or in combination.
[0070] E-2-2. Crosslinking agent The pressure-sensitive adhesive composition may contain a crosslinking agent. As the crosslinking agent, an organic crosslinking agent, a polyfunctional metal chelate, etc. can be used. As the organic crosslinking agent, for example, an isocyanate crosslinking agent, a peroxide crosslinking agent, an epoxy crosslinking agent, and an imine crosslinking agent can be mentioned. The polyfunctional metal chelate is a compound in which a polyvalent metal is covalently bonded or coordinately bonded to an organic compound.
[0071] The amount of the crosslinking agent to be added is, for example, 0.01 to 5 parts by weight with respect to 100 parts by weight of the (meth)acrylic polymer.
[0072] E-2-3.Silane coupling agents The pressure-sensitive adhesive composition may contain a silane coupling agent. The silane coupling agent preferably contains a reactive functional group. The reactive functional group of the reactive functional group-containing silane coupling agent is typically a functional group other than an acid anhydride group. Examples of functional groups other than an acid anhydride group include an epoxy group, a mercapto group, an amino group, an isocyanate group, an isocyanurate group, a vinyl group, a styryl group, an acetoacetyl group, a ureido group, a thiourea group, a (meth)acrylic group, a heterocyclic group, and combinations thereof. The reactive functional group-containing silane coupling agents can be used alone or in combination.
[0073] The amount of the reactive functional group-containing silane coupling agent is usually 0.001 to 2 parts by weight based on 100 parts by weight of the (meth)acrylic polymer.
[0074] E-2-4.Additives The adhesive composition may contain an additive. Specific examples of additives include colorants, powders such as pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, antiaging agents, light stabilizers, UV absorbers, polymerization inhibitors, inorganic or organic fillers, metal powders, particles, and foils. In addition, a redox system may be used by adding a reducing agent within a controllable range. The type, number, combination, and content of additives may be appropriately set according to the purpose.
[0075] F. Image display device The optical laminate described in the above items A to E can be applied to an image display device. Therefore, the embodiment of the present invention also includes an image display device using such an optical laminate. Representative examples of the image display device include a liquid crystal display device and an organic EL display device. The image display device according to the embodiment of the present invention typically includes the optical laminate described in the above items A to E on the viewing side. EXAMPLES
[0076] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Measurement methods and evaluation methods in the examples are as follows.
[0077] (1) Thickness The thickness of 10 μm or less was measured using an interference film thickness meter (manufactured by Otsuka Electronics, product name "MCPD-3000"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C").
[0078] (2) Storage modulus For the adhesive layers (adhesives) used in the examples and comparative examples, dynamic viscoelasticity measurements were performed under the following conditions using an Advanced Rheometric Expansion System (ARES) manufactured by Rheometric Scientific, and the storage modulus was read from the measurement results. (Measurement conditions) Deformation mode: Torsion Measurement temperature: -40℃~150℃ Heating rate: 5℃ / min Measurement frequency: 1Hz
[0079] (3) Shrinkage rate The optical laminates obtained in the examples and comparative examples were cut into rectangles measuring 128 mm x 160 mm to prepare test samples. The test samples were conveniently divided into 32 mm square areas (total of 20), and the precise dimensions of the long and short sides of each area were measured using a Mitutoyo CNC image measuring instrument, and the average dimensions of each were calculated as S. LS0 and S SS0 After measuring the dimensions, the test sample was heated at 85°C for 240 hours, and the dimensions after heating were measured in the same manner. LS1 and S SS1 The shrinkage rate in the long side direction S LS is (S LS0 -S LS1 ) / S LS0 × 100. Shrinkage rate in the short side direction S SS is (S SS0 -S SS1 ) / S SS0 This was calculated by multiplying by 100.
[0080] (4) Uneven display The optical laminates obtained in the examples and comparative examples were attached to a glass plate via an adhesive layer to prepare test samples. The test samples were heated at 85°C for 500 hours, then placed on a reflector (manufactured by Toray Film Processing Co., Ltd., product name "Cerapeel DMS-X42", total light reflectance: 86%), and the reflected hue (L*a*b* color system) was measured using a CM2600-d (manufactured by Konica Minolta, Inc.). 2 +b 2 ) 1 / 2 The display unevenness in a high temperature environment was evaluated according to the following criteria. ○ (Good): Δab is less than 1.5 △(Intermediate): Δab is 1.5 or more and less than 2.5 × (Failure): Δab is 2.5 or more
[0081] [Production Example 1: Preparation of adhesive] (Preparation of Acrylic Polymer A1) A monomer mixture containing 99 parts of butyl acrylate and 1 part of 4-hydroxybutyl acrylate was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with 100 parts of ethyl acetate for 100 parts of this monomer mixture, and nitrogen gas was introduced while gently stirring to replace the atmosphere with nitrogen. The liquid temperature in the flask was kept at about 55°C, and a polymerization reaction was carried out for 8 hours to prepare a solution of acrylic polymer A1 with a weight average molecular weight (Mw) of 1.8 million and Mw / Mn=4.8.
[0082] (Preparation of Adhesive) 0.1 parts of trimethylolpropane / xylylene diisocyanate adduct (manufactured by Tosoh Corporation, product name "Takenate D110N"), 0.3 parts of peroxide crosslinking agent (manufactured by Nippon Oil & Fats Corporation, product name "Niper BMT"), and 0.2 parts of epoxy group-containing silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM-403") were blended with 100 parts of the solid content of the acrylic polymer A1 solution to obtain adhesive PSA1.
[0083] [Production Example 2: Preparation of adhesive] (Preparation of Acrylic Polymer A2) A monomer mixture containing 94.9 parts of butyl acrylate, 0.1 parts of 2-hydroxyethyl acrylate, and 5 parts of acrylic acid was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with 100 parts of ethyl acetate for 100 parts of this monomer mixture, and nitrogen gas was introduced while gently stirring to replace the atmosphere with nitrogen. The liquid temperature in the flask was kept at about 55°C, and a polymerization reaction was carried out for 8 hours to prepare a solution of acrylic polymer A2 with a weight average molecular weight (Mw) of 2.2 million and Mw / Mn=3.9.
[0084] (Preparation of Adhesive) 0.6 parts of trimethylolpropane / tolylene diisocyanate adduct (manufactured by Tosoh Corporation, product name "Coronate L"), 0.2 parts of peroxide crosslinking agent (manufactured by Nippon Oil & Fats Corporation, product name "Niper BMT"), and 0.2 parts of epoxy group-containing silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM-403") were blended with 100 parts of the solid content of the acrylic polymer A2 solution to obtain adhesive PSA2.
[0085] [Production Example 3: Preparation of adhesive] (Preparation of Prepolymer Composition) In a flask, 0.05 parts by weight of 2,2-dimethoxy-1,2-diphenyl-1-one (trade name "Omnirad651", manufactured by IGM Resins) as a first photopolymerization initiator and 0.05 parts by weight of 1-hydroxycyclohexyl phenyl ketone (trade name "Omnirad184", manufactured by IGM Resins) as a second photopolymerization initiator were added to a monomer mixture containing 60 parts by weight of n-octyl acrylate (NOAA), 30 parts by weight of butyl acrylate (BA), 8 parts by weight of 4-hydroxybutyl acrylate (4HBA), and 2 parts by weight of N-vinyl-2-pyrrolidone (NVP). The mixture was then irradiated with ultraviolet light in a nitrogen atmosphere to polymerize a portion of the monomer components in the mixture, thereby obtaining a prepolymer composition with a polymerization rate of approximately 10%.
[0086] (Preparation of Adhesive) 100 parts by weight of the prepolymer composition obtained above, 0.08 parts by weight of dipentaerythritol hexaacrylate (DPHA) as a crosslinking agent, 0.05 parts by weight of 2,2-dimethoxy-1,2-diphenyl-1-one (trade name "Omnirad651", manufactured by IGM Resins) as a photopolymerization initiator, and 0.3 parts by weight of a silane coupling agent (trade name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.) were mixed to obtain adhesive PSA3.
[0087] [Production Example 4: Preparation of polarizing plate] 1. Preparation of Polarizer As a thermoplastic resin substrate, a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a Tg of about 75° C. was used, and one side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched 2.4 times in the machine direction (longitudinal direction) in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the finally obtained polarizer would be the desired value (dyeing treatment). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4% by weight, potassium iodide concentration: 5% by weight) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, the film was dried in an oven maintained at about 90° C. while being brought into contact with a SUS heated roll whose surface temperature was maintained at about 75° C. (drying shrinkage treatment). In this manner, a polarizer having a thickness of about 5 μm was formed on the resin substrate, and a polarizing plate having a resin substrate / polarizer structure was obtained. The single transmittance Ts of the polarizer was 43.3%.
[0088] 2. Preparation of Polarizing Plates A biaxially stretched acrylic resin film (thickness: 20 μm) was attached to the surface of the obtained polarizer (the surface opposite to the resin substrate) via a UV-curable adhesive. The resin substrate was then peeled off to obtain a polarizing plate P1 having a biaxially stretched acrylic resin film (protective layer) / polarizer structure.
[0089] [Production Example 5: Preparation of polarizing plate] A polarizing plate P2 having a structure of unstretched cycloolefin resin (COP) film (thickness: 25 μm) was obtained in the same manner as in Production Example 4, except that an unstretched COP film (protective layer) / polarizer was used instead of the acrylic resin film.
[0090] [Production Example 6: Preparation of polarizing plate] A polarizing plate P3 having a structure of an obliquely stretched COP film (protective layer) / polarizer was obtained in the same manner as in Production Example 4, except that an obliquely stretched COP film (thickness: 25 μm) was used instead of the acrylic resin film.
[0091] [Production Example 7: Preparation of polarizing plate] 1. Preparation of Polarizer A long roll of polyvinyl alcohol (PVA) resin film (manufactured by Kuraray, product name "PE3000") with a thickness of 30 μm was uniaxially stretched in the longitudinal direction to 5.9 times its original size using a roll stretching machine while simultaneously undergoing swelling, dyeing, crosslinking, and washing processes, and finally a drying process to produce a polarizer with a thickness of 12 μm. Specifically, the film was stretched 2.2 times during the swelling treatment in pure water at 20°C. Next, the film was stretched 1.4 times during the dyeing treatment in an aqueous solution at 30°C in which the weight ratio of iodine to potassium iodide was 1:7, and the iodine concentration was adjusted so that the single transmittance of the resulting polarizer was 45.0%. Furthermore, a two-stage crosslinking treatment was adopted, and the film was stretched 1.2 times during the first stage crosslinking treatment in an aqueous solution at 40°C in which boric acid and potassium iodide were dissolved. The aqueous solution in the first stage crosslinking treatment had a boric acid content of 5.0% by weight and a potassium iodide content of 3.0% by weight. The film was stretched 1.6 times during the second stage crosslinking treatment in an aqueous solution at 65°C in which boric acid and potassium iodide were dissolved. The aqueous solution in the second stage crosslinking treatment had a boric acid content of 4.3% by weight and a potassium iodide content of 5.0% by weight. The cleaning treatment was performed with an aqueous potassium iodide solution at 20° C. The aqueous solution used for the cleaning treatment had a potassium iodide content of 2.6% by weight. Finally, the film was dried at 70° C. for 5 minutes to obtain a polarizer.
[0092] 2. Preparation of Polarizing Plates A TAC film (thickness: 25 μm) and an obliquely stretched COP film (thickness: 25 μm) were bonded to both sides of the above polarizer via a polyvinyl alcohol-based adhesive, to obtain a polarizing plate P4 having a structure of TAC film (protective layer) / polarizer / obliquely stretched COP film (protective layer).
[0093] [Example 1] 1. Preparation of the first retardation layer and the second retardation layer A photopolymerizable liquid crystal compound exhibiting a nematic liquid crystal phase (BASF's "Paliocolor LC242", chemical formula below) was dissolved in cyclopentanone to prepare a solution with a solid content concentration of 20% by weight. A leveling agent (DIC's "Megafac F-563"), a photopolymerization initiator (IGM Resins's "Omnirad907"), and a crosslinking agent (Shin-Nakamura Chemical Co., Ltd.'s "A-DCP") were added to this solution to prepare a coating liquid for forming a liquid crystal alignment solidified layer. An obliquely stretched COP film was prepared as a substrate. The above-mentioned coating liquid for forming a liquid crystal alignment solidified layer was applied onto this substrate by a spin coater, and the substrate was heated at 100°C for 3 minutes to align the liquid crystal compound. After cooling to room temperature, the substrate was exposed to a nitrogen atmosphere with an accumulated light dose of 600 mJ / cm. 2 The layer was then irradiated with ultraviolet light of 1.5 to 2.5 μm to perform photocuring, thereby fixing the alignment state of the liquid crystal compound. In this manner, a laminate of the substrate / first liquid crystal alignment solidified layer (thickness: 1.5 to 2.5 μm, Re(550): 270 nm) was obtained. A laminate of the substrate / second liquid crystal alignment solidified layer (thickness: 1.0 to 1.5 μm, Re(550): 140 nm) was obtained in the same manner as above, except that the coating thickness was changed. [ka]
[0094] 2. Preparation of the third retardation layer A liquid crystal coating solution was prepared by dissolving 20 parts by weight of a side-chain liquid crystal polymer having a weight average molecular weight of 5000 and the following chemical formula (n=0.35, and shown as a block polymer for convenience), 80 parts by weight of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: trade name Paliocolor LC242), and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: trade name Irgacure 907) in 200 parts by weight of cyclopentanone. The coating solution was then applied to a PET substrate that had been subjected to a vertical alignment treatment using a bar coater, and the liquid crystal was aligned by heating and drying at 80°C for 4 minutes. The liquid crystal layer was irradiated with ultraviolet light to harden the liquid crystal layer, forming a positive C plate (thickness 3 μm) on the substrate. [ka]
[0095] 3. Preparation of Optical Laminate The first retardation layer was attached to the polarizer surface of the polarizing plate P1 obtained in Production Example 4 via a UV-curable adhesive (thickness 1 μm), and then the substrate was peeled off. Next, the second retardation layer was attached to the surface of the first retardation layer via a UV-curable adhesive (thickness 1 μm), and the substrate was peeled off. Next, the third retardation layer was attached to the surface of the second retardation layer via a UV-curable adhesive (thickness 1 μm), and the substrate was peeled off. The adhesive PSA1 (thickness: 15 μm) obtained in Production Example 1 was placed on the peeling surface to obtain an optical laminate having a polarizing plate / first retardation layer / second retardation layer / third retardation layer / adhesive layer configuration. The T / E of the obtained optical laminate was 0.062. The obtained optical laminate was subjected to the above evaluations (3) and (4). The results are shown in Table 1.
[0096] [Examples 2 to 6 and Comparative Examples 1 to 6] An optical laminate was prepared by combining the polarizing plates and the pressure-sensitive adhesive layers as shown in Table 1. The obtained optical laminate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0097] [Table 1]
[0098] In Table 1, for example, the notation "acrylic" means that a protective layer of an acrylic resin film is disposed on one side of the polarizer, and the notation "COP / TAC" means that protective layers of a COP film and a TAC film are disposed on both sides of the polarizer, respectively. Furthermore, the notation "obliquely stretched" under "COP / TAC" means that the COP film is an obliquely stretched film.
[0099] As is clear from Table 1, according to the examples of the present invention, display unevenness in a high temperature environment is suppressed by optimizing the ratio T / E of the polarizer thickness T to the pressure-sensitive adhesive layer storage modulus E. Furthermore, it is clear that such an effect cannot be obtained by only adjusting either the polarizer thickness or the pressure-sensitive adhesive layer storage modulus. [Industrial Applicability]
[0100] The optical laminate according to the embodiment of the present invention can be suitably used in image display devices (typically, liquid crystal display devices and organic EL display devices). [Explanation of symbols]
[0101] 10 Polarizing plate 11 Polarizer 12 Protective layer 21 1st retardation layer 22 Second retardation layer 30 Adhesive layer 100 Optical laminate
Claims
1. A polarizing plate including a polarizer, a first retardation layer, a second retardation layer, and a pressure-sensitive adhesive layer in this order, The first retardation layer and the second retardation layer are each a liquid crystal alignment solidified layer, An optical laminate, in which a thickness T of the polarizer and a storage modulus E of the pressure-sensitive adhesive layer satisfy the following relationship: T / E≦0.100 (μm / kPa).
2. 2. The optical laminate according to claim 1, wherein the sum of the shrinkage percentage in a first direction and the shrinkage percentage in a second direction perpendicular to the first direction after heating at 85° C. for 240 hours is 0.80% or less.
3. 2. The optical laminate according to claim 1, wherein the pressure-sensitive adhesive layer has a storage modulus E of 70 kPa or more and / or the polarizer has a thickness T of 8 μm or less.
4. The first retardation layer has an Re(550) of 200 nm to 300 nm, and the angle between the slow axis of the first retardation layer and the absorption axis of the polarizer is 10° to 20°, The second retardation layer has an Re(550) of 100 nm to 190 nm, and the angle between the slow axis of the second retardation layer and the absorption axis of the polarizer is 70° to 80°. The optical laminate according to claim 1 .
5. The optical laminate according to claim 1 , further comprising a third retardation layer between the polarizing plate and the pressure-sensitive adhesive layer, the third retardation layer having refractive index characteristics that satisfy the relationship nz>nx=ny.
6. An image display device comprising the optical laminate according to claim 1 .
Citation Information
Patent Citations
Polarizing plate
JP2019120950A
Polarizing plate with retardation layer and adhesive layers, and organic electroluminescence display device using the same
JP2021063972A
Method for manufacturing long-sized wide-band wavelength film, and method for manufacturing long-sized circularly polarized film
JP2022052074A
Optical film with adhesive layer and image display device including optical film with adhesive layer
JP2022092281A
Polarizing plate and organic el display device
JP2022183881A